Penetration of electrostatic field through Faraday shield of ICRH strap antenna - Moiseenko, V.E. (Вопросы атомной науки и техники, 2005)
The penetration of electrostatic field outside the shield at the part the antenna faced to plasma is studied in the framework of two-dimensional numerical model. It is shown that single-layer Faraday shield does not have satisfactory shielding properties. The shielding can be improved sufficiently using overlaying two-layer shield. У рамках двовимірної числової моделі вивчено проникнення електростатичних полів крізь екран на його частині, що звернена до плазми. Показано, що одношаровий Фарадеївський екран не забезпечує екранування на прийнятному рівні. З використанням двошарового екрану екранування може бути суттєво поліпшене. В рамках двумерной численной модели изучено проникновение электростатических полей сквозь экран на его участке, обращенном к плазме. Показано, что однослойный Фарадеевский экран не обеспечивает экранирование на приемлемом уровне. С использованием двухслойного экрана экранирование может быть существенно улучшено.